FENOMENA CHILDFREE DALAM RUMAH TANGGA MUSLIM: TINJAUAN HUKUM KELUARGA ISLAM DAN HAK REPRODUKSI - Jasmin, Suriah Pebriyani; Syahrul, Muhammad (IAIN BONE, 2025)
The childfree phenomenon, or the conscious decision to remain childless, has emerged in contemporary Muslim family discourse. This decision is often viewed as a form of individual rights recognition, yet it also raises controversy within the context of Islamic family law, which emphasizes the importance of offspring in marriage. This article aims to examine the childfree phenomenon from the perspective of Islamic family law and reproductive rights, and assess the extent to which this choice aligns with or contradicts the maqÄá¹£id al-syarÄ«â€˜ah, particularly in the context of marriage objectives and the protection of lineage. This study employs a normative-qualitative approach by analyzing various sources of Islamic law, contemporary fiqh, and the views of scholars on reproductive rights and the purpose of marriage in Islam. The findings indicate that although Islam strongly emphasizes the importance of procreation through marriage, the decision not to have children (childfree) is not automatically contrary to Shariâ€˜ah. Such a decision, when made with clear consideration of maslahat (public interest) and without harm to others, may be regarded as permissible within Islamic law. This research proposes the need for an adaptive and responsive Islamic legal approach to contemporary social dynamics, while still upholding deep ethical principles of Islam, particularly in safeguarding family and societal values. Thus, childfree can be understood as a legitimate choice if it aligns with the principles of maslahat in the context of Muslim family life.